Psychological Burden and Associated Factors of the COVID-19 Pandemic on People in Quarantine and Isolation Centers in Ethiopia: A Cross-Sectional Study - Misgana, Tadesse; Tesfaye, Dejene; Tariku, Mandaras; Ali, Tilahun; Alemu, Daniel; Dessie, Yadeta (Frontiers in Psychiatry, 2022)
Background: Globally, a lot of countries put into practice early quarantine measures as the essential COVID-19 prevention mechanism. Other than physical effects, quarantine has a major result on mental health and well-being at both individual levels as well as community-level at large. Therefore, this study was designed to assess the mental health burden of COVID-19 on people in quarantine and isolation centers in Eastern Ethiopia. Method: A cross-sectional study was done among 423 suspected cases of COVID-19 pandemic that were in quarantine and isolation centers found in Eastern Ethiopia in 2020. Participants were selected by the convenience sampling method. The common mental disorder was measured by the “Self Reporting Questionnaire-20 (SRQ-20)”. Logistic regression was done to identify predictive factors and a P-value less than 0.05 was considered statistically significant. Results: The common mental disorder among suspected cases of COVID-19 in Ethiopia was found to be 13.5% (95% CI: 10.2, 17.1%). Female (AOR=1.52, 95% CI: 1.1, 2.92), known chronic medical illness (AOR= 7.0, 95% CI: 2.2, 21.8), inadequate accessibility of personal protective equipment (AOR= 6.1, 95% CI: 2.8, 13.3), poor awareness about the pandemic (AOR= 2.90, 95% CI: 2.71, 7.54), presence of symptoms of the disease (AOR=5.3, 95% CI: 2.57, 11.1), and substance use (AOR= 2.7, 95% CI: 1.2, 6.1) were found to be associated with a common mental disorder. Conclusions: The current study revealed that common mental disorder was relatively high among suspected cases of COVID-19 in quarantine and isolation centers as compared to the general populations. Female sex, preexisting medical illnesses, accessibility of PPE, awareness of the pandemic, symptoms of the disease, and using any type of substances were associated with a common mental disorder. Therefore, providing appropriate psychosocial intervention for the populations at risk is important to decrease the effect of common mental disorders among suspected cases of COVID-19.